Providing healthy diets for young children: the experience of parents in a UK inner city - Goldthorpe, Joanna (Int J Qual Stud Health Well-being, 2018)
Objectives: There is a consistent body of evidence to demonstrate that obesity in very early childhood tends to continue into adolescence and through to adulthood. Parental practices in relation to food can have an effect on this trajectory, however existing studies reporting on interventions for treating obesity suggest there is a need to involve populations from demographically diverse backgrounds childhood obesity research. Design/Methods: A qualitative study was carried out using semi-structured interviews with parents in a deprived inner city area. Results: Although parents had good intentions towards providing a health diet for their chidren, a number of barriers emerged. Findings were reported in relation to the following themes: information and education; barriers (having a child with special needs, children’s food preferences and using food to promote desirable behaviour) and techniques (household rules & routines, setting limits and parameters, modelling and food preparation). Conclusion: Parents and carers would benefit from targeted interventions based on improving techniques around food parenting practices, with a focus on equipping parents with the skills to overcome barriers encountered not only in early childhood, but as children progress to school age and through to adolescence.